Implementation of Digital Literacy to Improve the Academic Competence of Students in Islamic Religious Universities - Habibi, Habibi (Al-Fikru: Jurnal Ilmiah, 2025)
The rapid digital transformation that is changing the academic lives of students, raises the need for digital literacy as a fundamental competency to compete in the technological era. However, many educational institutions, especially religious institutions in the regions, still face weaknesses in the systematic implementation of digital literacy. This study aims to explore the implementation of digital literacy in improving students' academic competencies at STAI Serdang Lubuk Pakam, with a focus on Islamic religious education. The research method used is a phenomenological approach to understand the experiences of students and lecturers in the use of digital literacy in the learning process. The results showed that digital literacy implementation strategies include digital task-based curriculum integration, lecturer capacity building, and collaborative learning. Despite barriers related to access and resistance to technology, the implementation of digital literacy succeeded in strengthening students' academic and religious competencies. The implications of this study provide recommendations for the development of inclusive access policies, continuous training for lecturers, and evaluations that pay attention to ethical aspects and religious values in digital literacy.